Concerning Predation on Small Vertebrates by Alien Gold Morph Midas cichlid, Amphilophus citrinellus (Cichlidae) - Mohamad Aqmal-Naser; Amirrudin B. Ahmad (Tropical Life Sciences Research, 2024)
Neotropical cichlid possesses territorial aggression which explains their success as alien species that pose threats to local fauna. The feeding ecology of Midas cichlid, Amphilophus citrinellus species outside its native range had never been fully understood. We aim to determine the stomach content, length-weight relationship and condition factor of this non-native species in one of the agroecosystems in Malaysia. The fish was collected using a cast net, and the guts were dissected. The stomach content (n = 35) revealed Midas cichlids feed on a wide array of preys including fish, amphibian and gastropod. The b-value is 2.60 (negative allometric growth) and the relative condition factor, Kn is 1.04. This result represents an initial study on the feeding aspect of this cichlid. Subsequent and continued researches are needed to evaluate the feeding behaviour and prey preferences of this species in its introduced range.